Recurrence of Endometrial Stromal Sarcoma, Two Decades Post-Treatment - Gangireddy, Mounika (Cureus, 2020)
Endometrial stromal cell sarcomas (ESS) are a unique subtype of uterine malignancy. Recurrent low grade endometrial stromal sarcomas (LESS) is identified in half of the patients. Here, we discuss a case of a 76-year-old Asian female with a past medical history of adenomyosis and hypertension who presented to the outpatient clinic with a chief complaint of painless hematuria for one day. Computed tomography scan of abdomen and pelvis with contrast showed a new right-sided mixed cystic and solid pelvic mass measuring up to 6 cm, obstructing and invading the distal right ureter, which was concerning for malignancy. Positron emission tomography (PET scan) demonstrated a right pelvic mass with increased radiotracer activity consistent with malignancy. She underwent laparotomy with excision of the right-sided pelvic mass with an abdominal washout and at the same time, also underwent cystoscopy with right ureteral stent placement. Tissue pathology was consistent with spindle cell neoplasm with staining and histologic features consistent with a recurrent stromal cell sarcoma. Uterine sarcomas tend to have an aggressive nature but there are key features about ESS that distinguish it from other uterine sarcomas. ESS has a more indolent clinical course and can reoccur years after initial diagnosis. They usually relapse locally, although relapses in extra-uterine sites have also been reported. Treatment of ESS depends on the grade and stage at the time of diagnosis. The main line of treatment for ESS consists of a total abdominal hysterectomy (TAH) and salpingo-oophorectomy (BSO). The significance of this case demonstrates that, although remission can be obtained after the initial diagnosis, recurrence can happen. Even when patients seem to be disease-free, clinicians should follow them closely; early diagnosis is important as treatment for this type of entity has a high survival rate.